2019
DOI: 10.4236/anp.2019.84005
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of Propolis Nanoparticles on Ehrlich Ascites Carcinoma Bearing Mice

Abstract: Background and objective Previous studies have demonstrated the anti-cancer effects of propolis. However, its use is limited because of its poor bioavailability. In the present study, the major objective was to improve propolis bioavailability using a nanosuspension formulation. The cytotoxic effect of propolis nanosuspension (PRO-NS) on the Ehrlich ascites carcinoma (EAC) in female Swiss albino mice was investigated in comparison to the free propolis. Materials and methods A propolis-loaded nanosuspension was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Similarly, in a recent study by Abdo et al (2019) [57], the cytotoxic effect of propolis and propolis nanoparticles on ehrlich as cites carcinoma cells has been shown.…”
Section: Effects Of Eep and Pragnps On Pc-3 Cell Viabilitymentioning
confidence: 58%
“…Similarly, in a recent study by Abdo et al (2019) [57], the cytotoxic effect of propolis and propolis nanoparticles on ehrlich as cites carcinoma cells has been shown.…”
Section: Effects Of Eep and Pragnps On Pc-3 Cell Viabilitymentioning
confidence: 58%
“…The challenging goal of cancer research continuously is discovering safe and effective new natural and synthetic products with anti-cancer effects . Plant-derived natural products have incredible potential to control cancer cell growth .…”
Section: Discussionmentioning
confidence: 99%
“…The challenging goal of cancer research continuously is discovering safe and effective new natural and synthetic products with anti-cancer effects. 15 Plant-derived natural products have incredible potential to control cancer cell growth. 16 Previous studies confirmed that the ASLE contained flavonoids, alkaloids, saponins, tannins, glycosides, steroids, phenols, and various acetogenin compounds and demonstrated a various array of pharmacological activities involving antioxidant, anti-cancer, and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is attributed to the heightened activity of superoxide dismutase (SOD) and increased glutathione content observed in the liver and EAC cells. These outcomes are thought to result from the prevention of oxidative damage, immune stimulation, and the induction of apoptosis [ 103 ]. In Table 3 , we have comprehensively summarized the activity of various types of cancer from different Propolis and solvents.…”
Section: Pharmacological Actions Of Nanopropolis In Various Diseases ...mentioning
confidence: 99%